In vivo Hox binding specificity revealed by systematic changes to a single cis regulatory module - Carlos Sánchez-Higueras (Nature Portfolio, 2019)
Hox proteins are expressed in partially overlapping regions to inform development along the embryo’s head-tail axis. Here the authors analyse a cis regulatory module directly regulated by seven different Drosophila Hox proteins to uncover how different Hox class proteins differentially control its expression.